Aiaa Aviation 2021 Forum 2021
DOI: 10.2514/6.2021-2467
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Performance of an Aircraft with Aft-Fuselage Boundary Layer Ingestion Propulsion

Abstract: Boundary Layer Ingestion (BLI) is a technology that promises fuel consumption benefits for future civil aircraft. However, it introduces detrimental aerodynamic interactions between the propulsor and the airframe. In particular, the inflow to the BLI propulsor is affected by the flow around the airframe elements. The non-uniform inflow can influence the fan aerodynamic, aeroacoustic and aeroelastic performance. As a consequence, the fan design needs to tolerate the inlet distortions in all the flight phases. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The findings underscored the substantial impact of FPR on the required shaft power, revealing that a 10% reduction in FPR resulted in a remarkable 36% reduction in shaft power. On the other hand, a series of experimental studies confirmed preliminary simulations of this PFC aircraft [215][216][217]. Particle image velocimetry techniques were employed to investigate the main aerodynamic phenomena, and the power balance method was employed to evaluate the aerodynamic and propulsive forces.…”
Section: Propulsive Fuselage Conceptsmentioning
confidence: 86%
“…The findings underscored the substantial impact of FPR on the required shaft power, revealing that a 10% reduction in FPR resulted in a remarkable 36% reduction in shaft power. On the other hand, a series of experimental studies confirmed preliminary simulations of this PFC aircraft [215][216][217]. Particle image velocimetry techniques were employed to investigate the main aerodynamic phenomena, and the power balance method was employed to evaluate the aerodynamic and propulsive forces.…”
Section: Propulsive Fuselage Conceptsmentioning
confidence: 86%
“…In this paper, the use of the power balance method as the theoretical framework to determine the benefits of BLI ensured minimal impacts from Reynolds number variations, thereby allowing for the scaling of low-speed results to actual flight Reynolds numbers [16][17][18]. In recent years, experimental investigations have placed an emphasis on axi-symmetric PFC aircraft [19,20]. These studies focused on characterizing the flowfield surrounding the BLI propulsor and on evaluating the aerodynamic forces and moments under various flight conditions.…”
Section: Introductionmentioning
confidence: 99%